Development of instrumented soccer footwear for kicking analysis and training purposes - Weizman, Y.; Fuss, F. K. (Procedia Engineering, 2015)
The kicking action in different ball sports is a prime skill that can decide the success of a team. The magnitude of the kick force and the movement of the centre of pressure (COP) during the impact phase between the soccer ball and the foot were determined by developing a novel low-cost pressure sensing system. This system was calibrated by a Kistler force plate and then validated for a range of forces (368-2146N). The COP was tested for two curve kicks at about 1100 N and the movement of the COP results showed similarity in the pattern (COPx = ±5 mm; COPy = ±10 mm). In addition, the COP data were displayed on a 4D colour-coded vector diagram model of a soccer boot. From the system calibration data, the coefficient of determination was found to be r^2max = 0.9882, r^2min =0.9333. For validating the system the measured and calculated forces were correlated (r^2 = 0.9125). The system is useful for counting the number of kicks, assessing the magnitude of the kick force, displaying the COP on the boot and correlating the COP and force to kicking accuracy.